School Leadership Practices and Teachers’ Job Commitment in Public Secondary Schools in Gombe State - Tsoho Aliyu Abraham (JOURNAL OF HUMANITIES AND SOCIAL POLICY, 2026)
This study examined the relationship between school leadership practices and teachers’ job commitment in public secondary schools in Gombe State, Nigeria. The study was motivated by persistent concerns regarding declining teacher morale, absenteeism, low instructional dedication, and inadequate participation in school activities across public secondary schools in Nigeria. The study adopted a descriptive survey research design. The population comprised principals and teachers in public secondary schools in Gombe State. A sample of 400 respondents was selected using a multistage sampling technique. Data were collected using a structured questionnaire titled School Leadership Practices and Teachers’ Job Commitment Questionnaire (SLPTJCQ). The instrument was validated by experts in Educational Management and Measurement and Evaluation, while reliability was established using Cronbach Alpha with a reliability coefficient of 0.84. Data were analyzed using mean and standard deviation to answer the research questions, while Pearson Product Moment Correlation (PPMC) was used to test the hypotheses at 0.05 level of significance. Findings revealed that transformational leadership, participative leadership, instructional leadership, and communication practices significantly influenced teachers’ job commitment in public secondary schools in Gombe State. The study concluded that effective school leadership practices are critical determinants of teachers’ commitment to duty and overall school effectiveness. The study recommended that school principals should adopt participative and transformational leadership approaches, strengthen communication channels, and provide supportive working environments that encourage teacher motivation and commitment.